2022
DOI: 10.3390/jcm11175231
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life (HRQoL) and the Effect on Outcome in Patients Presenting with Coronary Artery Disease and Treated with Percutaneous Coronary Intervention (PCI): Differences Noted by Sex and Age

Abstract: Background and aim: poor quality of life (QoL) has been identified as an independent risk factor for mortality and major cardiac events (MACE) in patients with cardiovascular disease (CVD). The aim of this study was to assess health-related quality of life (HRQoL) at baseline and its association with outcome in patients with coronary artery disease presenting for percutaneous coronary intervention (PCI). The outcome was measured by mortality and MACE at 1-year, and whether there was any difference for sex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
0
3
0
6
Order By: Relevance
“…Індекс маси тіла (ІМТ) становив (тут і далі -медіана (Ме), міжквартильний інтервал [МКІ]) 29,1 (26,8) кг/м 2 . Надмірна маса тіла (ІМТ 25-29,9 кг/м 2 ) була у 39 (46 %) випадках.…”
Section: матеріали і методиunclassified
See 2 more Smart Citations
“…Індекс маси тіла (ІМТ) становив (тут і далі -медіана (Ме), міжквартильний інтервал [МКІ]) 29,1 (26,8) кг/м 2 . Надмірна маса тіла (ІМТ 25-29,9 кг/м 2 ) була у 39 (46 %) випадках.…”
Section: матеріали і методиunclassified
“…Отримані нами дані щодо старшого віку як предиктора клінічно значущого поліпшення ЯЖ після ПКВ (за показником РНsum), загалом, узгоджуються з даними літератури про те, що пацієнти старших вікових груп можуть мати користь від реваскуляризації міокарда, зокрема в контексті покращання фізичного компонента здоровʼя [7,26]. До того ж початково гірша ЯЖ в таких пацієнтів, цілком імовірно, підвищуватиме шанси на суттєвіше її поліпшення після процедури (у нашому випадку − збільшення РНsum на величину ≥ 7,4 бала, яка перевищує запропонований у літературі «пороговий» рівень [18]), що може відображати ефект власне ПКВ (аналогічно до підсумків дослідження ORBITA-2 [25]).…”
Section: обговоренняunclassified
See 1 more Smart Citation
“…6,8,13 The manifestations of cardiac pain and associated symptoms contribute to substantial morbidity and impairments in health-related quality of life (HRQoL) in women. 14,15 The complex presentation of CAD in women presents a challenge for timely detection and management of symptoms. Recent data have shown that women often delay seeking medical care when experiencing acute cardiac pain and/or associated symptoms, with time between symptom onset to emergency department arrival being 85-320 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Any unplanned cardiac rehospitalization in the first year post-PCI was strongly associated with an increased all-cause mortality rate (HR 2.50, 95% CI 1.67 to 3.75; p < 0.001). Finally, in the third study by Conradie et al, an attempt was made to assess health-related quality of life (HRQoL) at baseline and its association with outcomes in patients with CAD undergoing PCI [ 8 ]. The EQ-5D-5L and VAS patient survey were utilized for the assessment of baseline HRQoL.…”
mentioning
confidence: 99%